Efeito do alumínio e da proporção NO³/NH₄ sobre a composição do nitrogênio solúvel em sorgo - Cambraia, José; E Trejo Chandías, José; Sant'Anna, Renato; de Moura Estevão, Marcio (Revista Ceres, 2025)
The effects of aluminum and of the NO3/NH4 ratio of the nutrient solution on the fresh matter yield and on the soluble nitrogen composition were studied in two sorghum cultivars.